2020
DOI: 10.3390/ijms21030700
|View full text |Cite
|
Sign up to set email alerts
|

Potential Clinical Implications of miR-1 and miR-21 in Heart Disease and Cardioprotection

Abstract: The interest in non-coding RNAs, which started more than a decade ago, has still not weakened. A wealth of experimental and clinical studies has suggested the potential of non-coding RNAs, especially the short-sized microRNAs (miRs), to be used as the new generation of therapeutic targets and biomarkers of cardiovascular disease, an ever-growing public health issue in the modern world. Among the hundreds of miRs characterized so far, microRNA-1 (miR-1) and microRNA-21 (miR-21) have received some attention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 179 publications
(292 reference statements)
0
81
0
3
Order By: Relevance
“…Furthermore, the Wnt pathway, which was also targeted in our study, is involved in endothelial injury, macrophage activation, and vascular smooth muscle migration, and these processes are closely associated with onset and progression of atherosclerosis ( 36 ). Previous studies showed that miR-1 is associated with cardiac injury and cardioprotection, and is increased in patients suffering from AMI ( 37 ). miR-142 is increased in atherosclerotic plaques and regulates oxLDL-induced apoptosis in macrophages; moreover, it can be used to predict major adverse cardiovascular events in CAD patients ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Wnt pathway, which was also targeted in our study, is involved in endothelial injury, macrophage activation, and vascular smooth muscle migration, and these processes are closely associated with onset and progression of atherosclerosis ( 36 ). Previous studies showed that miR-1 is associated with cardiac injury and cardioprotection, and is increased in patients suffering from AMI ( 37 ). miR-142 is increased in atherosclerotic plaques and regulates oxLDL-induced apoptosis in macrophages; moreover, it can be used to predict major adverse cardiovascular events in CAD patients ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since non-coding RNAs have been widely implicated in various cellular activities and disease etiologies, non-coding RNA-based gene therapy is considered as a new approach to treat them. In the heart, several miRNAs are dysregulated during cardiac I/R injury, which may be treated as key regulators or biomarkers in these cardiac diseases (Colpaert and Calore 2019;Kura et al 2020). For example, dysregulation of miR-1, miR-21, and miR-133 was observed in MI heart tissue.…”
Section: A B Cmentioning
confidence: 99%
“…Although the precise role of miR-1 is still uncertain in cardiac I/R injury, it is undeniable that miR-1 is closely related to the myocardial I/R processes, and may regulate the adaptive mechanisms after heart injury (Kura et al 2020). Other important regulators of cardiac I/R injury include miR-21 and miR-133, which are believed to exert cardioprotective functions in MI, mainly through inhibition of apoptosis (Colpaert and Calore 2019;Kura et al 2020). Combined with our study, down-regulated miR-129 was detected in vivo after I/R injury, when compared with the Sham group.…”
Section: A B Cmentioning
confidence: 99%
See 2 more Smart Citations